2021
DOI: 10.1136/bmjpo-2020-000761
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre survey of retinopathy of prematurity in Indonesia

Abstract: BackgroundThe incidence of retinopathy of prematurity (ROP) is higher in Indonesia than in high-income countries. In order to reduce the incidence of the disease, a protocol on preventing, screening and treating ROP was published in Indonesia in 2010. To assist the practical implementation of the protocol, meetings were held in all Indonesia regions, calling attention to the high incidence of ROP and the methods to reduce it. In addition, national health insurance was introduced in 2014, making ROP screening a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Methods to detect infants at risk of progressing ROP is, therefore, of the utmost importance. In a recent Indonesian survey, we found that the incidence of Type 1 ROP in teaching hospitals in infants born <28 weeks was 16 to 22%, and 10% in infants born after 28-32 weeks [2]. These numbers are much higher compared to high-income countries.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Methods to detect infants at risk of progressing ROP is, therefore, of the utmost importance. In a recent Indonesian survey, we found that the incidence of Type 1 ROP in teaching hospitals in infants born <28 weeks was 16 to 22%, and 10% in infants born after 28-32 weeks [2]. These numbers are much higher compared to high-income countries.…”
Section: Discussionmentioning
confidence: 84%
“…Screening for ROP is usually performed by ophthalmologists specifically trained to do so. However, trained ophthalmologists are not always present in many hospitals in low and middle-income countries (LMIC), such as Indonesia, that care for preterm infants [2]. It is crucial, therefore, to develop alternative methods or models to identify those infants who are at risk of developing Type 1 ROP.…”
Section: Introductionmentioning
confidence: 99%
“…In the <1000 g group, 27 (46%) infants had no ROP, 22 (37%) had ROP 1-2 and 10 (17%) had ROP 3-5. In the 1000-1500 g group, 172 (68%) infants had no ROP, 71 (28%) had ROP 1-2 and nine (4%) had ROP 3-5 [42].…”
Section: Epidemiologymentioning
confidence: 96%
“…1 Multicentre study of 34 hospitals in 17 major provinces in Indonesia showed that the incidence of all-stage ROP was 18% and severe ROP was 4%. 3 The Early Treatment for Retinopathy of Prematurity (ETROP) study reported that type 1 ROP was indicated early management, such as laser ablation within 48 -72 hours of the first diagnosis. However, some eyes treated progressed to stage 4 and 5 ROP.…”
Section: Introductionmentioning
confidence: 99%